Public Transportation Development in Smart Forest City Based on Cloud Computing - Li Ya (Forest Chemicals Review, 1970)
The intelligent level of public transportation in smart forest city is an important symbol of urbandevelopment and industrial manufacturing development. Urban road network in smart forestcity is a kind of complex network. Complex network theory is an important branch of complexsystematic science. At first, complex networks are used to describe the interrelated theories innatural and Social Sciences and engineering technology. Later, they have been widely used inother fields, and become one of the hot topics in many disciplines. This paper uses the theory ofcomplex network knowledge, combined with the intelligent algorithm developed in moderntimes, to generate and optimize the urban public transport network. The optimization of urbanpublic transport network is mainly for the convenience of residents' travel and urbandevelopment. Starting from the topological structure, this paper analyzes the mutual attractionrelationship of public transport traffic volume between nodes, and combines with geneticalgorithm to determine the optimal route selection. Finally, we get the urban public transportnetwork to meet the urban development and residents' travel needs.